GE_GERICHTE P/12868/2015 vom 16. September 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;ABUS DE CONFIANCE;ESCROQUERIE;SOLIDARITÉ PASSIVE | CP.138; CP.146; CPP.122; CO.41; CO.492; CO.493; CO.143; CPP.442.al4